– Statodynamic exercises in self-rehabilitation of post-stroke patients at home - Yudenko, I.E. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effectiveness of using statodynamic physical exercises in the self-rehabilitation of persons who have suffered a cerebral stroke. Methods and structure of the study. Subject to the study were a total of 19 persons (mean age - 58.5±7.3 years) who suffered a cerebral stroke and underwent a rehabilitation course at the Department of Neuro-Rehabilitation of the Surgut Clinical Psychoneurological Hospital. To determine whether the developed complex of statodynamic exercises is effective, we measured the functional indicators (heart rate, blood pressure), tolerance to hypoxia using Stange and Gençhe’s tests, as well as the parameters characterizing the efficiency of physical rehabilitation: goniometry and dynamometry of the paretic arm, the level of muscle spasticity on the Ashworth Scale. Results and conclusions. The study findings indicate that it is appropriate to use the developed complex of statodynamic exercises in the post-stroke rehabilitation. There were statistically significant changes (at p<0.05) in most functional indicators, as well as in the parameters characterizing the efficiency of physical rehabilitation, which significantly improved the quality of everyday social and household activities of the patients.